2020
DOI: 10.1177/1203475420908250
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Communication About Topical Corticosteroids: A Quality Improvement Study

Abstract: Background Patients are often non-adherent to topical corticosteroids (TCS). This may be in part due to poor communication between patients and dermatologists. Objectives This quality improvement (QI) study aims to describe dermatologist–patient communication about TCS treatments and to compare communication before and after the implementation of an educational intervention. Methods This QI study assesses the communication between dermatologists and new dermatology outpatients receiving a TCS prescription in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 51 publications
2
0
0
Order By: Relevance
“…However, aggregating values of DR and PI to account for the whole consultation had not been done previously. Studies using MEDICODE that have showed variations between consultations have shown variation in specific themes as opposed to the whole consultation 31 32. This appeared to be the case again here.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…However, aggregating values of DR and PI to account for the whole consultation had not been done previously. Studies using MEDICODE that have showed variations between consultations have shown variation in specific themes as opposed to the whole consultation 31 32. This appeared to be the case again here.…”
Section: Discussionsupporting
confidence: 65%
“…Studies using MEDICODE that have showed variations between consultations have shown variation in specific themes as opposed to the whole consultation. 31 32 This appeared to be the case again here. The intervention group discussed emotional issues 28 times as opposed to the TAU group’s 12.…”
Section: Discussionsupporting
confidence: 57%